OVERWEIGHT AND OBESITY AS RISK FACTORS FOR CHEMOTHERAPY-INDUCED HEPATOTOXICITY IN PATIENTS WITH ACUTE LYMPHOBLASTIC LEUKEMIA - Skrypnyk, I.M.; Maslova, G.S.; Lymanets, T.V. (World of Medicine and Biology, 2022)
Obesity is one of the proven risk factors for all types of tumors and is one of the reasons for reducing the effectiveness of specific chemotherapy and the development of chemotherapy-induced injury of liver. This article presents the results of functional liver state monitoring in patients with acute lymphoblastic leukemia during remission induction chemotherapy, taking into account the overweight and obesity. High toxicity of acute lymphoblastic leukemia chemotherapy regimens with a general tendency to hypoproteinemia development has been demonstrated. The overweight and obesity potentiate cytostatic-induced liver injury in patients with acute lymphoblastic leukemia with maximum risk in case of primary liver injury due to tumor exposure.